Metformin-mediated effects on mesenchymal stem cells and mechanisms: proliferation, differentiation and aging - Liu, Xinjuan; Li, Zekun; Liu, Luyun; Zhang, Ping; Wang, Yue; Ding, Gang (Frontiers in Pharmacology, 2024)
Mesenchymal stem cells (MSCs) are a type of pluripotent adult stem cell with strong self-renewal and multi-differentiation abilities. Their excellent biological traits, minimal immunogenicity, and abundant availability have made them the perfect seed cells for treating a wide range of diseases. After more than 60 years of clinical practice, metformin is currently one of the most commonly used hypoglycaemic drugs for type 2 diabetes in clinical practice. In addition, metformin has shown great potential in the treatment of various systemic diseases except for type 2 diabetes in recent years, and the mechanisms are involved with antioxidant stress, anti-inflammatory, and induced autophagy, etc. This article reviews the effects and the underlying mechanisms of metformin on the biological properties, including proliferation, multi-differentiation, and aging, of MSCs in vitro and in vivo with the aim of providing theoretical support for in-depth scientific research and clinical applications in MSCs-mediated disease treatment.